Ammonia removal from aqueous solution by membrane distillation. (18th October 2012) - Duong, Tuan; Xie, Zongli; Ng, Derrick; Hoang, Manh
Abstract Environmental regulation, increased pressure on water resources and rising cost for wastewater discharges make wastewater treatment for recycling an essential investment for many industries. Ammonia is a major pollutant in many industrial and agricultural wastewaters, and its elimination is essential for wastewater to be reused or meeting local discharge standards. In this study, the removal of ammonia from dilute aqueous solution has been investigated using sweep gas and vacuum membrane distillation (SGMD and VMD). Factors that affect the separation process such as feed and air flow rates, vacuum degree and feed temperature have been investigated. Overall, mass transfer coefficients (Kov) were calculated, and the results indicated that Kov for VMD is higher than that for SGMD under similar operation. Overall, ammonia mass transfer coefficient up to 12.06 × 10−5 and 5.63 × 10−5 m/s can be achieved for VMD and SGMD, respectively. The ammonia removal efficiency was enhanced by increasing sweep gas flow rate or by decreasing downstream pressure.